2012
DOI: 10.1007/s00403-012-1238-0
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenin levels are increased in lesional skin and sera in patients with erythrodermic cutaneous T cell lymphoma

Abstract: Angiogenin is a member of the ribonuclease superfamily that is associated with the angiogenic process. Angiogenesis is regarded as an important step to support primary and metastatic tumor growth. In cutaneous T cell lymphoma (CTCL), angiogenesis in lesional skin is increased, suggesting that interaction between tumor cells and their microvasculature are likely to occur during progression of CTCL. Patients with hematological malignancies show increased serum angiogenin levels, which are related with poor overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Similarly, in CTCL, angiogenesis, assessed either by microvessel density or by microvessel number in lesional skin, is increased, suggesting that interaction between tumour cells and their microvasculature is likely to occur during the progression of CTCL (8,9). Consistent with those reports, increased expression of angiogenin, one of the angiogenic factors, in the sera and lesional skin was reported in patients with erythrodermic CTCL (10). Serum levels of angiopoietin-2 (Ang-2), which has the capacity to promote both angiogenesis and lymphangiogenesis, are also elevated in patients with SS and are correlated with disease severity markers (11).…”
supporting
confidence: 79%
“…Similarly, in CTCL, angiogenesis, assessed either by microvessel density or by microvessel number in lesional skin, is increased, suggesting that interaction between tumour cells and their microvasculature is likely to occur during the progression of CTCL (8,9). Consistent with those reports, increased expression of angiogenin, one of the angiogenic factors, in the sera and lesional skin was reported in patients with erythrodermic CTCL (10). Serum levels of angiopoietin-2 (Ang-2), which has the capacity to promote both angiogenesis and lymphangiogenesis, are also elevated in patients with SS and are correlated with disease severity markers (11).…”
supporting
confidence: 79%
“…It was reported that serum angiogenin levels increase in patients with cutaneous T cell lymphoma, and the molecule is thought to act as an inhibitor of polymorphonuclear leukocyte degranulation (20). Elevated levels of angiogenin have also been detected in the sera of patients with pancreatic cancer and from 5 DM patients, 4 CADM patients and 5 SLE patients, mean relative transcript levels of angiogenin in skin tissues from DM/CADM patients were significantly up-regulated compared with the values in normal skin (p = 0.007 and 0.014, respectively) and SLE skin (p = 0.009 and 0.014, respectively) ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Tumor cells of MF or SS expressed vascular endothelial growth factor (VEGF), which plays a central role in tumor‐associated angiogenesis, through Janus kinase 3 and the c‐Jun N‐terminal kinase‐dependent signal pathways . Expression of angiogenin, which is a member of the ribonuclease superfamily that is associated with the angiogenic process, was also elevated in lesional skin of erythrodermic MF or SS . The main sources of angiogenin were keratinocytes, endothelial cells and infiltrating T cells .…”
Section: Angiogenesismentioning
confidence: 99%
“…Expression of angiogenin, which is a member of the ribonuclease superfamily that is associated with the angiogenic process, was also elevated in lesional skin of erythrodermic MF or SS . The main sources of angiogenin were keratinocytes, endothelial cells and infiltrating T cells . Angiopoietin‐2 (Ang‐2) is one of the ligands for the endothelium‐specific tyrosine kinase Tie2 receptor and involved in angiogenesis alongside VEGF .…”
Section: Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation